2018
DOI: 10.1177/0020764018766561
|View full text |Cite
|
Sign up to set email alerts
|

Factors influencing the level of self-stigmatisation in people with mental illness

Abstract: According to our results, with regard to the factors that were followed, self-stigmatisation correlates with the presence of employment (social inclusion), duration of illness in patients with psychosis and treatment adherence. We did not find a statistically significant influence of age, gender, marital status or clinical diagnosis on the level of self-stigma.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
16
0
2

Year Published

2020
2020
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 19 publications
(18 citation statements)
references
References 41 publications
(56 reference statements)
0
16
0
2
Order By: Relevance
“…Previous research suggests younger people report more mental illness-related stigma [11,12], while those with higher levels of education are more likely to conceal their diagnosis [9]. Some studies show a gender effect but the evidence is inconsistent [10,[13][14][15][16][17][18]. Some evidence suggests a mediating role for social support, with increased peer support helping to challenge internalised stigma related to mental illness [19].…”
Section: Factors Associated With Stigmamentioning
confidence: 99%
“…Previous research suggests younger people report more mental illness-related stigma [11,12], while those with higher levels of education are more likely to conceal their diagnosis [9]. Some studies show a gender effect but the evidence is inconsistent [10,[13][14][15][16][17][18]. Some evidence suggests a mediating role for social support, with increased peer support helping to challenge internalised stigma related to mental illness [19].…”
Section: Factors Associated With Stigmamentioning
confidence: 99%
“…[ 32 33 ] Therefore, perceived social support is crucial for individuals with SUDs to enhance coping strategies and buffer against stigma. Moreover, we found that unemployed people had a greater perceived stigma, which is consistent with the studies of Kalisov et al .,[ 34 ] and da Silveira et al[ 21 ] reported that individuals who did not attend a workplace or are unemployed often reported high levels of stigma experiences. A possible explanation is that individuals with SUDs or with substance use history are perceived more negatively as weak moral character, lacked capacity, dishonest, and reduced social inclusion, which lead to not engaged in community events, including employment.…”
Section: Discussionmentioning
confidence: 99%
“…A possible explanation is that individuals with SUDs or with substance use history are perceived more negatively as weak moral character, lacked capacity, dishonest, and reduced social inclusion, which lead to not engaged in community events, including employment. [ 21 34 35 ] These may impact an individual's access to employment opportunities or employer's hiring decisions. [ 36 ] Then, consequently contributes to a further increase in stigma internalization.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Especially, if a mental disorder is not associated with hope for recovery, but experienced as a threat to basic needs, a dysfunctional self‐stigmatisation can result (Zhang et al, 2017). This is associated with poor recovery and an overall negative therapy outcome in various psychiatric patients (Kalisova, Michalec, Hadjipapanicolaou, & Raboch, 2018), especially in schizophrenia (Häfner, 2017). Further influencing factors of self‐stigmatization are younger age (Werner, Aviv, & Barak, 2008), unemployment and the number of episodes of mental disorders (Adewuya, Owoeye, Erinfolami, & Ola, 2011).…”
Section: Introductionmentioning
confidence: 99%